REGULATORY STRINGENCY, CORPORATE GOVERNANCE AND FIRM PROFITABILITY: STATIC PANEL ANALYSIS OF INSURANCE COMPANIESIN NIGERIA USING RANDOM EFFECTS APPROACH - Adedeji Daniel Gbadebo (Gusau Journal of Accounting and Finance)
This study investigates the influence of corporate board characteristics on the profitability of listed insurance firms inNigeria, witha particular focus on the moderatingeffect ofregulatorystringency. Usingbalanced panel data covering10 firms from2014 to2023, the researchapplies a randomeffectsregression model to explore the relationshipsamong board size, board composition, gender diversity, meeting frequency, and financial expertise in relation to return on assets (ROA). The analysis also incorporates firm-specific controls and regulatory stringency indices to examine conditional effects. Descriptive statistics reveal moderate variability across governance attributes, while correlationand multicollinearitydiagnostics confirmstatistical validity. The results indicate that board gender diversity and financial expertise significantly influence firm profitability, with regulatory stringency negatively moderating the relationship. Findings align with agency and resource dependence theories,emphasizingthedualroleofgovernance qualityand externalinstitutionalconstraints.This research contributes to the evolving discourse on corporate governance in emerging markets by offering evidence-based insights into board dynamics under varying regulatory intensities. The study recommends targeted reforms to improve board capacity while recognizing the need for adaptive regulatory frameworks that support firm performance.